2020
DOI: 10.3390/su12072966
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Performance Decay of Permeable Asphalt Mixture in Seasonally Frozen Regions under Freeze-Thaw Cycles

Abstract: This paper focuses on the freeze-thaw cycles (F-T cycles) resistance of porous asphalt mixture (PAM) with different air voids in order to explore the gradation of the PAM suitable for seasonal freezing regions. Three sets of PAMs with 18%, 21%, and 25% air voids were designed. After 0–20 F-T cycles, the effects of F-T cycles on the performance degradation of three groups of PAMs were studied by performing a low-temperature splitting test with acoustic emission technology, a normal temperature splitting test, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Regarding discontinuous surfaces in polar zones, certain interlocking paving systems have been shown to tolerate snow plowing equipment [62]. These temperaturedynamic climates favor pavements with low air void percentages, which tend to offer more tensile and compression strength [67]. While many published results are encouraging, the field needs generalized durability models with demonstrated accuracy across stress factors, climates, and amounts of recycled (and other eco-friendly) materials.…”
Section: Durability In Operating Environmentmentioning
confidence: 99%
“…Regarding discontinuous surfaces in polar zones, certain interlocking paving systems have been shown to tolerate snow plowing equipment [62]. These temperaturedynamic climates favor pavements with low air void percentages, which tend to offer more tensile and compression strength [67]. While many published results are encouraging, the field needs generalized durability models with demonstrated accuracy across stress factors, climates, and amounts of recycled (and other eco-friendly) materials.…”
Section: Durability In Operating Environmentmentioning
confidence: 99%
“…The holistic vision for infiltration rate is to broadly realize positive impacts on the ecosystem and stormwater network. Research by Newman et al confirmed that high-biodiversity can be present in and under pervious pavement systems [67], yet future refinements such as jump-starting the microbiological development in pervious pavements after installation are needed, as well as creative uses (and management) of sub-base water reservoiring. With flourishing microorganisms, organic materials clogging passageways are decomposed, sequestered oils are broken down, plants and soil-dwelling organisms are fed, and beauty and bounty proceed up the food chain.…”
Section: Initial Hydraulic Performancementioning
confidence: 99%
“…To better apply asphalt mixtures to the northeast seasonal frozen regions, a series of studies have been carried out toward exploring the F-T destruction characteristics of asphalt mixtures [ 29 , 30 , 31 , 32 ]. In addition, many scholars conducted various experiments of asphalt mixtures under varying F-T actions to explore the damage evolution [ 33 , 34 , 35 ]. Tarefder et al [ 36 ] analyzed the influences of F-T action on the fatigue and rheometer of asphalt mixtures using several experimental methods.…”
Section: Introductionmentioning
confidence: 99%